Variant type is associated with disease characteristics in SDHB, SDHC and SDHD-linked phaeochromocytoma–paraganglioma. Issue 2 (6th September 2019) - Bayley, Jean Pierre; Bausch, Birke; Rijken, Johannes Adriaan; van Hulsteijn, Leonie Theresia; Jansen, Jeroen C; Ascher, David; Pires, Douglas Eduardo Valente; Hes, Frederik J; Hensen, Erik F; Corssmit, Eleonora P M; Devilee, Peter; Neumann, Hartmut P H
Abstract : Background: Pathogenic germline variants in subunits of succinate dehydrogenase ( SDHB, SDHC and SDHD ) are broadly associated with disease subtypes of phaeochromocytoma–paraganglioma (PPGL) syndrome. Our objective was to investigate the role of variant type (ie, missense vs truncating) in determining tumour phenotype. Methods: Three independent datasets comprising 950 PPGL and head and neck paraganglioma (HNPGL) patients were analysed for associations of variant type with tumour type and age-related tumour risk. All patients were carriers of pathogenic germline variants in the SDHB, SDHC or SDHD genes. Results: Truncating SDH variants were significantly over-represented in clinical cases compared with missense variants, and carriers of SDHD truncating variants had a significantly higher risk for PPGL (p<0.001), an earlier age of diagnosis (p<0.0001) and a greater risk for PPGL/HNPGL comorbidity compared with carriers of missense variants. Carriers of SDHB truncating variants displayed a trend towards increased risk of PPGL, and all three SDH genes showed a trend towards over-representation of missense variants in HNPGL cases. Overall, variant types conferred PPGL risk in the (highest-to-lowest) sequence SDHB truncating, SDHB missense, SDHD truncating and SDHD missense, with the opposite pattern apparent for HNPGL (p<0.001). Conclusions: SDHD truncating variants represent a distinct group, with a clinical phenotype reminiscent of but not identical to SDHB . We propose that surveillance and counselling of carriers of SDHD should be tailored by variant type. The clinical impact of truncating SDHx variants is distinct from missense variants and suggests that residual SDH protein subunit function determines risk and site of disease.